Site characterization and systems analysis in Central Mekong - Staal, Steven J.; Njiru, Nelly M.; Thinh Nguyen; Kihoro, Esther; Karimov, A.A.; Teufel, Nils; Wijk, Mark T. van; Ritzema, Randall S. (World Agroforestry Centre, 2016)
The systems addressed in this chapter and in the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics) broadly include natural systems comprising biophysical, resource and climate realities; social systems made up of people, societies and their institutions; and, what some term as artificial systems built on elements of the first two (Checkland 1981). Agricultural systems, for example, modify natural systems for productive use, add infrastructure to provide markets, and modify human institutions to organize labour and services to enable the agricultural system to function. Regardless of how systems are categorized, they can be simplistically deconstructed into components and the interactions between them. In this chapter we characterize some of the Central Mekong systems, and also address some of the system dynamics, at two basic levels of resolution. Section 2 addresses regional agricultural systems consisting of one or more districts within a country, and includes variations in natural and social systems in addition to agricultural systems. Five regional cases that reflect the diversity across the Central Mekong Action Area are examined and compared. The authors focus on systems at the community or local landscape level, particularly the individual farm household component, and the variation between households within the landscape. Variables include household agricultural practices, household resources, capacity, and links to markets and institutions. Section 3 looks at diversity in the variables among farm households and the implications for livelihoods and well-being. Section 4 examines food security levels arising from specific farm household strategies and performance, how the two are related, and the implications for potential farm interventions. We conclude by comparing the types of systems examined, the differences in types of tools needed, and the differences in questions asked and learning generated. Throughout this chapter, authors refer to data from reports and articles that interested readers can find in Annex I.